EVALUATION OF ANTIDIARRHEAL ACTIVITY OF ETHANOLIC LEAF EXTRACT OF ERIOBOTRYA JAPONICA LINDL - KAMADYAAPA, DAVIE JUWA; Gondwe, Mavuto Masopera; Shauli, Mathulo; SEWANI-RUSIKE, CONSTANCE; Iputo, Jehu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The study was carried out to investigate the antidiarrheal activity of ethanolic leaf extract of Eriobotrya japonica (EEJ) using various models of experimental diarrhea. Methods: Antidiarrheal property of EEJ at 100, 200, and 400 mg/kg/bwt was evaluated using castor oil-induced diarrhea, castor oil-induced enteropooling, and gastrointestinal propulsive models of experimental diarrhea in Sprague Dawley rats of both sexes, weighing 200–250 g. Cytotoxicity test of EEJ was performed using brine shrimp bioassay. Results: Toxicity assay of EEJ showed a lethal concentration value of 1225 μg/ml suggesting non-toxicity. EEJ significantly (p<0.05) and dose-dependently (100, 200 and 400 mg/kg/bwt) inhibited castor oil-induced diarrhea by 38.1%, 76.19%, and 100%, respectively, and enteropooling by 28%, 56%, and 88%, respectively, compared with control. Pre-treatment with yohimbine, α2-adrenoceptor blocker significantly reversed the protective effect of EEJ (400 mg/kg) against castor oil-induced diarrhea and against castor oil-induced enteropooling, suggesting the involvement of α2-adrenoceptors in antidiarrheal property of EEJ. Furthermore, EEJ significantly (p<0.05) and dosedependently (100, 200, and 400 mg/Kg/bwt) inhibited gastrointestinal motility by 28%, 62%, and 83.92%, respectively. Conclusion: The study has demonstrated the antidiarrheal potential of ethanolic leaf extract of EEJ, which may be attributable to its dual antisecretory and antimotility activities probably through activation of the sympathetic α2-adrenergic pathway.